2018
DOI: 10.4049/jimmunol.1700956
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 IFN Induction by Cytosolic Nucleic Acid Is Intact in Neonatal Mononuclear Cells, Contrasting Starkly with Neonatal Hyporesponsiveness to TLR Ligation Due to Independence from Endosome-Mediated IRF3 Activation

Abstract: Two million infants die each year from infectious diseases before they reach 12 mo; many of these diseases are vaccine preventable in older populations. Pattern recognition receptors represent the critical front-line defense against pathogens. Evidence suggests that the innate immune system does not fully develop until puberty, contributing to impaired response to infection and impaired vaccine responses in neonates, infants, and children. The activity of the pattern recognition receptor family of cytosolic nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 51 publications
3
16
0
Order By: Relevance
“…Deficiencies in the responses to TLR activation in children is an example of how the immune system of children and adults differs [12,13]. We have recently reported that Poly(I:C) and Poly(dA:dT), activators of the cytosolic nucleic acid sensors of the innate immune system, can activate the immune systems of neonates and infants as efficiently as in adults [9]. Given that many of the adjuvants in current use rely on activating TLR pathways, we hypothesise that Poly(I:C) or Poly(dA:dT) may be candidates for future childhood vaccines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deficiencies in the responses to TLR activation in children is an example of how the immune system of children and adults differs [12,13]. We have recently reported that Poly(I:C) and Poly(dA:dT), activators of the cytosolic nucleic acid sensors of the innate immune system, can activate the immune systems of neonates and infants as efficiently as in adults [9]. Given that many of the adjuvants in current use rely on activating TLR pathways, we hypothesise that Poly(I:C) or Poly(dA:dT) may be candidates for future childhood vaccines.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently identified a potential novel adjuvant for childhood vaccines. In adults, Poly(I:C) or Poly(dA:dT), when transfected in to cells, activate cytosolic nucleic acid (CNA) sensors and induce Type I Interferon (IFN) production along with other proinflammatory cytokines such as Tumor Necrosis Factor α (TNFα) [9]. It has previously been shown that while other activators of the innate immune system such as Lipopolysaccharide (LPS) and CpG, TLR4 and 9 ligands respectively, function well in adults, they are less able to activate the immune system of neonates and young children [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…This highlights that our protocol represents a robust alternative to protein-based assays (e.g., when measuring changes in cytokine mRNA expression in PBMCs in response to specific in vitro stimulation). This work will significantly improve analytical capacity of studies relying on irreplaceable, relatively small or costly human samples (e.g., neonatal PBMCs) (66,67).…”
Section: Discussionmentioning
confidence: 99%
“…21,22 In addition, cell-surface TLR ligation (i.e., TLR4) is impaired by a failure to endocytose after ligation by lack of Rab11a activity in neonates. 23 Of interest, even children up to 5 years old still exhibit lower IL-12 production upon PBMC stimulation with TLR agonists than adults, but are still higher than neonates. 24 This implies that some limitations in either TLR or epigenetic regulation continue even past toddlerhood.…”
Section: Pathogen Recognitionmentioning
confidence: 99%
“…However, TLR signaling is known to be limited in innate immune cells of newborns . In addition, cell‐surface TLR ligation (i.e., TLR4) is impaired by a failure to endocytose after ligation by lack of Rab11a activity in neonates . Of interest, even children up to 5 years old still exhibit lower IL‐12 production upon PBMC stimulation with TLR agonists than adults, but are still higher than neonates .…”
Section: Innate Antipathogen Responsesmentioning
confidence: 99%